Reticulocyte Hemoglobin Equivalent (RET-HE) As A Predictor and Early Marker for Oral Iron Response in Iron Deficiency Anemia Patients - Ketut Suega; I Made Bakta (Journal of Global Pharma Technology, 2018)
This study was aimed to determine whether Ret-He has a role for early detection and as a predictor factor for treatment response in iron deficiency anemia patient after oral iron therapy in 4 weeks. Iron deficiency anemia (IDA) patient were diagnosed based on hypochromic microcytic anemia with ferritin level < 20 ng/ml. All patients were taking oral iron pill for 4 weeks. Hemoglobin serum, absolute reticulocyte count (ARC), Ret-He, MCV, MCH, MCHC, and hematocrit were measured. Responders are defined as patients who reach total changes of their hemoglobin level > 2 g/dl in 4 weeks. Data analysis was done by SPSS. There were 26 IDA patients consisted of 15 (57.7%) female and 11 (42.3%) male patients with mean of age was 47.31. Before treatment, level of Ret-He, absolute reticulocyte count, HB, HCT and MCV were 18.16 pg (SD 4.43), 0.67 (SD 3.02), 7.94 g/dl (0.74), 26.5 % (SD 2.48), 64.9 fl (SD 0.51) respectively. There was 18 (69.2%) patient considered as responders and 8 (30.8%) patients considered as non-responders. The evaluation showed all markers were increased except for absolute reticulocyte level. On adjusted multiple logistic regression, the only variable that found statistically significant was Ret-He at week 1 with p= 0.031; 95% CI 0.349-0.950. It is suggested that reticulocyte hemoglobin equivalent (Ret-He) proved to be an early and sensitive predictor for oral iron therapy response in patients with iron deficiency anemia. Keywords: Ret-He, Treatment response, Iron deficiency anemia.